2015
DOI: 10.3389/fneur.2015.00209
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Motor Complex and Disturbed Motor Control – a Retrospective Clinical and Lesion Analysis of Patients after Anterior Cerebral Artery Stroke

Abstract: BackgroundBoth the supplementary motor complex (SMC), consisting of the supplementary motor area (SMA) proper, the pre-SMA, and the supplementary eye field, and the rostral cingulate cortex are supplied by the anterior cerebral artery (ACA) and are involved in higher motor control. The Bereitschaftspotential (BP) originates from the SMC and reflects cognitive preparation processes before volitional movements. ACA strokes may lead to impaired motor control in the absence of limb weakness and evoke an alien hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…In an interhemispheric FC study, stroke patients displayed decreased interhemispheric interaction in the CPL compared with that of HCs, and there was a significant positive correlation between the interhemispheric FC in the CPL and the FMA scores of the stroke patients (Tang et al, ). Therefore, the findings of abnormal activation in the SMA and CPL in the typical band indicated that the impairment in the cerebellar–cerebral information circuit may contribute to reduced hand function (O'Reilly, Beckmann, Tomassini, Ramnani, & Johansen‐Berg, ), and the poor hand function outcomes in CPH patients may be associated with dysfunctional motor control (Amengual et al, ; Brugger, Galovic, Weder, & Kägi, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an interhemispheric FC study, stroke patients displayed decreased interhemispheric interaction in the CPL compared with that of HCs, and there was a significant positive correlation between the interhemispheric FC in the CPL and the FMA scores of the stroke patients (Tang et al, ). Therefore, the findings of abnormal activation in the SMA and CPL in the typical band indicated that the impairment in the cerebellar–cerebral information circuit may contribute to reduced hand function (O'Reilly, Beckmann, Tomassini, Ramnani, & Johansen‐Berg, ), and the poor hand function outcomes in CPH patients may be associated with dysfunctional motor control (Amengual et al, ; Brugger, Galovic, Weder, & Kägi, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ReHo values in the bilateral CPL were positively correlated with FMA-HW scores, and that in the contralesional SMA was negatively correlated with FMA-HW scores. Therefore, the findings of abnormal activation in the SMA and CPL in the typical band indicated that the impairment in the cerebellar-cerebral information circuit may contribute to reduced hand function (O'Reilly, Beckmann, Tomassini, Ramnani, & Johansen-Berg, 2010), and the poor hand function outcomes in CPH patients may be associated with dysfunctional motor control (Amengual et al, 2014;Brugger, Galovic, Weder, & Kägi, 2015). Patients with motor conversion disorder showed abnormal activity in the SMA during motor preparation compared to that of normal volunteers (Voon, Brezing, Gallea, & Hallett, 2011).…”
Section: Full Band Analysis Of Rehomentioning
confidence: 99%
“…The study's aim was mainly to test for the feasibility of graded fMRI neurofeedback training of the SMA in first time MCA stroke patients. The SMA is an attractive target region of interest (ROI) in MCA stroke patients because it is supplied by the anterior cerebral artery (Brugger et al, 2015 ) and thus is not expected to have (substantially) compromised hemodynamic function following MCA stroke. Our first hypothesis was that patients could activate the SMA through motor imagery.…”
Section: Introductionmentioning
confidence: 99%
“…The SMC is assumed to keep the balance between motor initiation and motor suppression [ 9 ]. Its relevance for gait control is underpinned by the occurrence of FOG-like gait patterns in patients with SMC lesions [ 10 , 11 ]. It is not surprising that the SMC is considered to play a central role in PD and, in particular, in PD-related gait impairment.…”
Section: Introductionmentioning
confidence: 99%